Double centralizing theorem for wreath products of the alternating group. Issue 2 (1st February 2019) - Kireeva, Elena
Abstract: The double centralizing theorem between the action of the symmetric group Sn and the action of the general linear group on the tensor space Tn ( W ) was obtained by Schur. Here we obtain a double centralizing theorem when Sn is replaced by the wreath product of a finite group G and the alternating group An .